2013
DOI: 10.1016/j.geb.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle and competitive bidding

Abstract: In an experiment using two-bidder first-price sealed-bid auctions with symmetric independent private values and 400 participants, we collected information on the female participants' menstrual cycles and the use of hormonal contraceptives. We find that naturally cycling women bid significantly higher than men and earn significantly lower profits than men except during the midcycle when fecundity is highest. We suggest an evolutionary hypothesis according to which women are predisposed by hormones to generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 85 publications
5
59
1
Order By: Relevance
“…Further, we explore the correlation between menstrual cycle phase and our primary outcome measures in the naturally cycling placebo group. Earlier studies on the menstrual cycle and economic preferences report inconclusive and sometimes contradictory results (e.g., Buser 2012b, Chen et al 2013, Pearson and Schipper 2013, Wozniak et al 2014 but mainly rely on self-reported menstrual cycle data, which can be expected to be less reliable than using hormonal data to define cycle phases. In our analysis with hormonal measurements, we find no significant relation between menstrual cycle phase and altruism, financial risk taking, or willingness to compete.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, we explore the correlation between menstrual cycle phase and our primary outcome measures in the naturally cycling placebo group. Earlier studies on the menstrual cycle and economic preferences report inconclusive and sometimes contradictory results (e.g., Buser 2012b, Chen et al 2013, Pearson and Schipper 2013, Wozniak et al 2014 but mainly rely on self-reported menstrual cycle data, which can be expected to be less reliable than using hormonal data to define cycle phases. In our analysis with hormonal measurements, we find no significant relation between menstrual cycle phase and altruism, financial risk taking, or willingness to compete.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have found hormonal variation over the menstrual cycle to relate to risk taking (Bröder andHohmann 2003, Chavanne andGallup 1998; see also Buser 2012b and Schipper 2014 for null results), competitiveness (Buser 2012b, Wozniak et al 2014, behavior in social preference games (Buser 2012a), loss aversion (Lazzaro et al 2016), and competitive bidding (Pearson andSchipper 2013, Schipper 2015). Taken together, this literature suggests that hormones associated with fertility and reproduction, like those in OCs, may affect important economic preferences.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, women's responses to competitive situations have also been linked to their testosterone levels (Bateup et al 2002), as well as to their menstrual cycles and contraceptive pill usage (Chen, Katuščák, and Ozdenoren 2013, Pearson and Schipper 2013, Wozniak, Harbaugh, and Mayr 2014. Bateup et al (2002) find, for example, that in the leadup to a competitive match, female rugby players experience an anticipatory rise in testosterone that is positively associated with increased self-reported focus and team bonding.…”
Section: Hormones and Fundamental Economic Preferencesmentioning
confidence: 99%